2023
DOI: 10.31234/osf.io/b3865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The learning bias for cross-category harmony is sensitive to semantic similarity: Evidence from artificial language learning experiments

Abstract: Cross-category harmony is one of the most well-known typological universals. It describes the tendency for syntactic heads to be ordered consistently relative to their dependents across different phrase types. Explanations for this universal vary as to whether cognitive factors play a role, or instead the tendency is due to mechanisms of language change alone. In this paper we report a series of artificial language learning experiments that aim to test a hypothesized link between cognition and cross-category h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Taking this a step further, training could also be conducted on one category of dependents and tested on a different category of dependents, taking the task from a generalisation to an extrapolation context. For example, training participants on the order between adjectives and nouns and then testing them on the order of genitives and nouns, similar to what is done in Wang et al (2023) where participants extrapolate the order between ad-jectives and nouns to the order between verbs and objects (and vice versa).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking this a step further, training could also be conducted on one category of dependents and tested on a different category of dependents, taking the task from a generalisation to an extrapolation context. For example, training participants on the order between adjectives and nouns and then testing them on the order of genitives and nouns, similar to what is done in Wang et al (2023) where participants extrapolate the order between ad-jectives and nouns to the order between verbs and objects (and vice versa).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, children do not learn all linguistic categories or constructions simultaneously (Gentner, 1982;Tardif et al, 1999), but must integrate these into an existing system which already might include similar constructions and categories or not. Extrapolation is often used in experimental tasks as well, in order to see how participants use limited or ambiguous evidence to generate novel items/structures or treat novel categories (e.g., Culbertson and Adger, 2014;Finley, 2018;Saldana et al, 2021;Wang et al, 2023).…”
Section: Memorisingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has explored the way that cognitive biases, which favour or disfavour certain linguistic structures, have contributed to the cross-linguistic typological tendency for harmonic word order (Christiansen, 2000;Culbertson, 2012;Culbertson & Kirby, 2016;Wang et al, 2023). This work includes experimental, computational and corpus-based studies examining how these structural biases emerge, and how they affect linguistic behaviour across different age groups and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, artificial language learning experiments examining this pattern have found that people tend to prefer harmonic languages to non-harmonic ones: both adults and children learn, reproduce and regularise (i.e., extend) harmonic patterns rather than non-harmonic ones (Culbertson & Newport, 2017;Culbertson et al, 2012), even if their native languages are non-harmonic (Culbertson, Franck, et al, 2020;Culbertson & Newport, 2015;Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%